Lactic acid bacteria: bacteriocin producer: a mini review - Alhaji Yusuf, Moshood; Tengku Abdul Hamid, Tengku Haziyamin (International Organization of Scientific Research (IOSR), 2013)
Summary: LAB is a diverse bacterial group consisting of 11 genuses. These bacteria are Gram-positive, non-spore-forming, coccus or rods but aerotolerant, able to ferment carbohydrates into energy and lactic acid. Lactic acid bacteria produce various compounds such as organic acids, diacetyl, hydrogen peroxide, and bacteriocins or bactericidal proteins during lactic acid fermentations. Bacteriocins are peptides produced by a variety of microbes and have antimicrobial activity against closely related species. These antimicrobial agents are gaining more and more attention as an alternative therapeutics not only in pharmaceutical but also as a preservative in food industries. The main aim of this review is to highlight lactic acid bacteria and its bacteriocins.